2022
DOI: 10.1126/sciimmunol.abl9929
|View full text |Cite
|
Sign up to set email alerts
|

Administration of aerosolized SARS-CoV-2 to K18-hACE2 mice uncouples respiratory infection from fatal neuroinvasion

Abstract: The development of a tractable small animal model faithfully reproducing human coronavirus disease 2019 pathogenesis would arguably meet a pressing need in biomedical research. Thus far, most investigators have used transgenic mice expressing the human ACE2 in epithelial cells (K18-hACE2 transgenic mice) that are intranasally instilled with a liquid severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) suspension under deep anesthesia. Unfortunately, this experimental approach results in disproportionat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
70
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 74 publications
14
70
1
Order By: Relevance
“…It has already been shown that vaccination partly protects against the development of long COVID [99]. Other variables that might influence the development of CNS disease include, for example, the infection dose and primary replication site of the virus [73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has already been shown that vaccination partly protects against the development of long COVID [99]. Other variables that might influence the development of CNS disease include, for example, the infection dose and primary replication site of the virus [73].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multifocal microgliosis and astrogliosis were reported in older patients [71], although it could not be ruled out that these were associated with host factors [72]. Perivascular and parenchymal infiltrations of CD8 + cytotoxic T cells and macrophages have been reported postmortem in patients with COVID-19 and in intranasally inoculated mice at 6 days post inoculation [61,71,73]. Extensive inflammatory responses, such as astrogliosis, activation of microglia, and perivascular cuffing of T cells, were detected postmortem in both white and gray matter of patient brains regardless of their COVID-19 disease severity, a finding that appeared most pronounced in the cranial medulla oblongata and olfactory bulb [74].…”
Section: Neurovirulencementioning
confidence: 99%
See 1 more Smart Citation
“…These limitations may be addressed by further modifications of the CC founder mouse models engineered to express hACE2 under more normal physiological conditions as has been achieved with humanization of the mouse Ace2 gene, H353K 61 . In addition, recent reports of limited CNS infection in K18-hACE2 mice infected with SARS-CoV-2 via aerosolized route of inoculation indicating that optimized experimental procedures may further improve the mouse model 62 . Alternatively, many of the strain backgrounds used here (including WSB) demonstrated relatively low levels of neuro-invasion and could be further evaluated as a more useful model of certain COVID-19 associated pathology, including the disorder known as long-COVID.…”
Section: Discussionmentioning
confidence: 99%
“…However, the confounding impact of neuroinvasion and neurodissemination and its role in the clinical decline of SARS-CoV-2 infected K18-hACE2 mice is becoming more readily acknowledged [ 41 , 42 , 43 , 44 ]. Furthermore, administration of aerosolized SARS-CoV-2 to K18-hACE2 mice resulted solely in respiratory infection and limited clinical disease at 6 days post infection (6 dpi) in contrast with those inoculated intranasally, suggesting that severe clinical outcome in K18-hACE2 mice is attributed to CNS disease [ 45 ].…”
Section: Introductionmentioning
confidence: 99%